GUIDANCE AND COUNSELING SERVICES IN DEVELOPING STUDENT HAPPINESS: SYSTEMATIC LITERATURE REVIEW - Ari Kurniawan; Mamat Supriatna; Yusi Riksa Yustiana (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
The guidance and counseling service approach in recent studies is no longer only focused on problems, but many have focused on individual strengths and lead to individual optimization. One of them is happiness. This study aims to obtain an overview of effective guidance and counseling services in developing students' happiness. The method used is Systematic Literature Review by identifying, evaluating, and interpreting all relevant research results related to research questions from both journals and theses and dissertations in 2015-2021 timeframe. Data analysis used meta-synthesis techniques, namely identifying, and interpreting the overall research results according to the research questions. The findings of this study are that there are various guidance and counseling service interventions that have a significant and effective effect on developing students' happiness.Keywords: happiness, guidance and counseling, students